Door Lock System Using Fingerprint - Mohd, Mohd Sabani; Ahmat Kamil, M. Hazmie; Mohamad, M. Khairul Nazmi; Razali, M. Aizat (Multidisciplinary Applied Research and Innovation, 2022)
On this report, the significance of the proper security level is being highlighted due to the security concern on the crimes activities which are surprisingly increased over a year. The thief and robbery activities that kept happening among the citizens are the proof that the security level that is used nowadays are still weak and not entirely effective to restrain the problems or constrains that related to the security concern. It can even cause traumatized among the victims or worse causing death. So, this paper is intended solely to introduce the most secure modern device that is used widely on the premise or buildings to protect its nature, which is the fingerprint sensor. It is able to make verification by using fingertip which is the one of the biometric identification that is used to verify the user. So, the problems such as lost, theft or duplicate or anything else that are often heard when they were using the conventional key to open the door can be solved. Moreover, this paper will also include the main objective, which is to design the prototype of the door lock system using fingerprint. Methodology that is being used are based on the SDLC process where all the 7 process involved to ensure the established system are stable and easy to use. Several important parts are described in detail such as the material, the methods, the designing process and also the implementation process with the aid of flowcharts and block diagrams. Furthermore, this paper also included the several experiments that is conducted mainly to learn in-depth on the characteristics of the related topics such as the accuracy of the fingerprint scanner, the range of Bluetooth module and also the entire system.